Status and redescription of the South American pest species Agrotis robusta (Lepidoptera: Noctuidae): a history of misidentifications - San Blas, Diego German (2013)
Agrotis robusta (Blanchard, 1852) (Lepidoptera: Noctuidae) is a species of economic importance in South America. This species is considered a pest on seedlings of several crops. Agrotis robusta is commonly confused with and treated as A. malefida Guenée in Boisduval and Guenée, 1852, and only a couple of works cite A. robusta for South America and none mention it as a species of economic importance. The aim of this work is to redescribe and illustrate the adult and male and female genitalia of A. robusta, and to provide an identification key to closely related pest species in South America with which A. robusta has been confused. Four new synonymies with A. robusta are established: A. aureolum Schaus, 1898, Scotia koehleri Berio, 1963, S. (Feltia) fulvaurea Köhler, 1966, and S. (F.) ancastiensis Köhler, 1966.